Marketing strategies of culinary products in improving family economy in the community of Al-Iman Islamic Boarding School, UluAle, Sidenreng Rappang Regency - Nur Hisani; Pratiwi Ramlan; Yusrianti Yusrianti; Damayanti Trisnasari (Universitas Muhammadiyah Enrekang, 2025)
This study aims to analyze the marketing strategy of culinary products and its influence on improving family economy in the Al-Iman Uluale Islamic Boarding School environment, Sidenreng Rappang Regency. The method used is quantitative descriptive with data collection techniques through questionnaires, interviews, observations, and documentation. The sample in this study was 38 families involved in culinary businesses in the Islamic boarding school environment.The results of the study showed that a marketing strategy that includes four main elements of product, price, place (distribution), and promotion (4P) has a significant effect on increasing sales. The simple linear regression test produced a coefficient of determination (R²) value of 0.619, which indicates that the marketing strategy contributed 61.9% to improving family economy. This finding indicates that an effective marketing strategy can increase family income and welfare in the Islamic boarding school environment.This study emphasizes the importance of product innovation, competitive pricing, easily accessible distribution, and active promotion, including the use of social media, in expanding the market and supporting the economic independence of families based on Islamic boarding school communities.